To Compare the Mean Postoperative Pain Score between Intravenous Paracetamol Vs Intravenous Ketorolac among patients undergoing Gynecological Abdominal Surgery - Sidra Chaudhary, Shahid Iqbal, Rifah Zia, Muhammad Muazzam Butt, Muhammad Baqir Ali Khan, Abaid-Ur-Rehman, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Post-operative pain is one of the common concerns in all the surgical interventions including gynecological surgeries. There is always a need for the agent with better efficacy and minimal side effect profiles. Aim: To compare the mean postoperative pain score between intravenous Paracetamol vs intravenous ketorolac among patients undergoing gynecological abdominal surgery Study design: Randomized Controlled Trial Setting & duration: Department of Anesthesia, Hameed Latif Hospital, Lahore from 12-06-2018 to 12-12-2018 Methodology: In this study, females with age 20 - 50 years with ASA I and II undergoing gynecological abdominal surgery were included. Group A was administered with intravenous paracetamol and group B with ketorolac. Pain was measured in terms of mean of numerical rating scale recorded at 12 hours postoperatively. Results: In the present study there were total 80 cases included, 40 in each group. The mean age in group B was 37.66±12.67 years and in group A was 41.29±11.36 years Mean post operative pain score was 3.05±0.61vs 3.56±0.89 in group B and A with p= 0.04 Mean post operative pain was 3.04±0.61 vs 3.51±0.77 with p= 0.03 in cases with BMI > 25. There was no significant difference in terms of type of procedure and mean pain score in both groups. Conclusion: Ketorolac is significantly better than Paracetamol in gynecological abdominal surgeries and this difference is also significantly better in cases with BMI > 25. Keywords: Pain, ketorolac, paracetamol, BMI